Measurement of radon concentration for models of living and non-living things in Samarra and its environs - Marwan Rasheed Abass (Tikrit Journal of Pure Science, 2023)
This research included a study of the proportion of radioactive elements naturally and in particular element of radioactive radon in parts of the body directly relevant to the lives of human organisms in Samarra and its surroundings , where collected samples from the teeth of human bones and some animals (cattle , sheep , goats and chickens , local fish and imported ) , as well as some of the pastes Tooth based on the principle that radioactive elements are concentrated in the bones for living organisms using reagents nuclear effect SSNTDs Results indicated that the largest gas radon concentration was in the bones of cows 1932 ± 162 and less concentration of radon was in a group dental age 45 years 198 ± 243 As for the toothpaste was the highest concentration in the teeth Sensodyne toothpaste 186 ± 150 and less concentration in toothpaste devoted 167 ± 123.